Recycling of spent lithium-ion batteries in view of green chemistry. Issue 17 (17th August 2021) - Li, Yukun; Lv, Weiguang; Huang, Hanlin; Yan, Wenyi; Li, Xiaokang; Ning, Pengge; Cao, Hongbin; Sun, Zhi
Abstract : This research could provide a guideline for implementing green chemistry principles into spent LIBs recycling. Abstract : Recycling of spent lithium-ion batteries (LIBs) is of great importance for both critical metal supply and environmental protection. Although the physical chemistry is still focused on pyrometallurgy, hydrometallurgy and electrometallurgy, state-of-the-art recycling technologies are a trend that is turning towards being more material/energy efficient in line with the principles of green chemistry. For instance, selective recycling of specified metals and direct regeneration of battery materials are being trialled to develop short-cut processes that prevent secondary pollution generation and improve the atomic economy during the whole recycling process. In this review, a number of technologies for recycling spent LIBs are overviewed, especially at different recycling stages to stepwise recover battery materials. It is clearly understood that extraction of critical metals and subsequent regeneration of materials are only part of the recycling process, while pretreatment to obtain black mass powder from battery cells and pollution control, in view of the recycling process to minimise environmental impact, are also extremely important. Furthermore, green design of batteries, as well as process design in view of the whole life cycle of LIBs, are topping the list of the research which requires profound and elaborate efforts. It is expected that this review could provide a guideline for implementing green chemistry principles into spent LIB recycling and stimulate further discussions on improving the green degree of the process.